A study of carbon nanodots (carbon quantum dots) synthesized from tangerine juice using one-step hydrothermal method. Issue 12 (2nd December 2021) - Aslan, Mikail; Eskalen, Hasan
Abstract: Carbon nanodots are one of the latest intriguing members of the nanocarbon family due to their improved aqueous solubility, low-cost production, good conductivity, nontoxic behavior, high biocompatibility, and eco-friendly nature in contrast to chemically derived carbon nanomaterials. In the present study, the water-soluble carbon nanodots were synthesized by using the one-step hydrothermal method. Tangerine juice was used as a carbon source. The synthesized carbon dots were characterized by X-ray diffraction, high-resolution transmission electron microscopy, UV-Vis spectrum and fluorescence spectra. DFT-based ab initio material modeling technique including the Van der Waals interactions was applied. The electronic properties were examined by DOS analysis. Although the geometrical shapes of carbon nanodots are known as quasi-spherical, according to the HR-TEM results, carbon nanodot particles that consist of cuboidal geometric shapes were found for the first time in this study. Moreover, the usability of the synthesized carbon nanodots in security ink applications has been investigated.